ANALISIS PENGEMBANGAN E-OFFICE DALAM PELAKSANAAN E-GOVERNMENT PADA DINAS KOMUNIKASI, STATISTIK DAN PERSANDIAN KOTA BEKASI - Mohamad Bintang; Muhammad Fadil (Governance, 2022)
E-government is the use of information technology that can help, improve relations between the government and other stakeholders, both to the community, business circles and fellow governments. This study aims to analyze the development and implementation of e-office and what factors hinder the implementation of e-office in the Bekasi City Communication, Information, Statistics and Encryption Service. This study uses a qualitative research method with a case study design because the research focuses on the development of e-office in the implementation of e-government at the Office of Communication, Information, Statistics and Encryption Bekasi City. Data collection techniques through observation, interviews and documentation. Informants in this study included the head of the e-government development section, the head of the e-government governance section, and e-government staff. The data obtained from the results of the study were reviewed using data reduction techniques, data presentation, and drawing conclusions. The results of this study indicate that the development of e-office is running well. This can be identified through the elements of successful e-government development which include support, capacity, value. From the support element, Diskominfostandi supports the development of e-office with the instructions issued by the Mayor of Bekasi Number: 555.10/1132/Diskominfostandi.Egov regarding the Implementation of Electronic Service Manuscripts Through E-office Applications in Bekasi City. From the capacity element, the information technology infrastructure owned by Diskominfostandi is sufficient, where Diskominfostandi currently has its own server to facilitate e-office users in the Bekasi City SKPD. From the value element, it is quite easy for users to write correspondence and archive letters. The inhibiting factor for the implementation of e-office at the Bekasi City Communication, Information, Statistics and Encryption Service is that human resources are still limited because they are still looking for a replacement programmer and when the head of the service wants to do an online signature published by the Electronic Certification Center (BSrE) it is constrained by the process inadequate network and also because there are too many users.